Citizen science in community-based watershed management: An institutional analysis in Ethiopia - Nigussie, L; Haile, AT; Gowing, J; Walker, D; Parkin, G (International Water Management Institute (IWMI), 2020)
Hydrometeorological monitoring can provide the information needed for early warning, and preparing and responding to weather-related natural disasters, thereby supporting development of the agriculture sector. This study examines the existing institutional arrangements for hydrometeorological monitoring and the practices followed by the Basin Development Authority and the National Meteorology Agency in Ethiopia. It also investigates the possibilities of embedding a citizen science approach into regular monitoring conducted by these organizations for addressing the hydrometeorological data gaps, particularly at micro-watershed levels.